2003
DOI: 10.1291/hypres.26.289
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Protein Intake and Blood Pressure in a Screened Cohort in Okinawa, Japan

Abstract: We examined the relation between protein intake and blood pressure in a screened cohort in Okinawa, Japan. A total of 1,299 screened subjects, 885 men and 414 women, were examined at the Okinawa General Health Maintenance Association. Daily intake of sodium (Na) and potassium (K) was estimated from Na, K,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Several previous studies reported an inverse association of total protein intake with systolic and/or diastolic blood pressure (1)(2)(3)(4)(5)(6)8). In the present study, total protein intake was inversely associated with both systolic and diastolic blood pressure; after further adjustment for nutritional factors, the association with diastolic blood pressure remained statistically significant.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Several previous studies reported an inverse association of total protein intake with systolic and/or diastolic blood pressure (1)(2)(3)(4)(5)(6)8). In the present study, total protein intake was inversely associated with both systolic and diastolic blood pressure; after further adjustment for nutritional factors, the association with diastolic blood pressure remained statistically significant.…”
Section: Discussionsupporting
confidence: 67%
“…Compared with previous Japanese and Chinese studies (6,8,9), we had a large number of subjects and conducted a more through adjustment for confounding variables. including alcohol intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Moreover, the average amount of protein we found in our population is comparable with the values reported in another study using the Maroni formula to estimate the amount of protein intake in a Japanese community-based cohort. 23 Another limitation of this study is that the protein intake we measure is susceptible to fluctuations because it reflects protein intake of only a few days before the urine collection; therefore, we based our protein intake on the average of two 24-h urine collections. In addition, we performed a sensitivity analysis including only individuals with a small difference in protein intake between the first and the second screening rounds.…”
Section: Discussionmentioning
confidence: 99%
“…1 This inverse association is also found in more recent studies. [2][3][4] However, results have been mixed when animal and plant proteins were examined separately. Cross-sectional studies conducted in rural Japanese 5,6 and Chinese 7,8 populations only found an inverse relationship between animal protein and BP, based on ratios of urinary excretions of sulphate and other animal protein-related amino acids.…”
Section: Introductionmentioning
confidence: 99%